Pragmatic aid management in fragile situations - France Bourgouin; Lars Engberg-Petersen (Danish Institute for International Studies (DIIS), 2013)
This report examines the relationship between aid management and results in the context of fragile situations. The success of aid-supported activities in fragile situations is highly uncertain. Yet, aid programmes sometimes succeed despite the adverse conditions. The report discusses the extent to which pragmatic aid management can explain relatively positive results based on an analysis of evaluations of reasonably successful aid-supported activities. Pragmatic aid management is conceptualised in terms of policy liberty, flexibility, responsiveness, context dependence and political sensitivity. The report concludes that, while a high degree of pragmatic aid management appears to be linked to relatively positive results of aid-supported activities, such aid management is rarely enough to count as success. Other factors are important as well. These include high-level political commitment, quality of aid management staff on the ground, and a process of transferring ownership and responsibility to actors and institutions in fragile societies.
Keywords: 300